Aluminum integral foam castings with microcellular cores by nano-functionalization - Hartmann, Johannes; Blümel, Christina; Ernst, Stefan; Fiegl, Tobias; Wirth, Karl-Ernst; Körner, Carolin (Journal of Materials Science, 2014)
The goal of the present work is the refinement of the pore morphology of aluminum integral foam castings. Integral foam molding, a modified high pressure die casting process, is used where a mixture of melt and blowing agent particles (magnesium hydride, MgH) is injected at high velocity into a permanent steel mold. At the mold surface, decomposition of the blowing agent and pore formation is suppressed due to the high solidification rate whereas solidification of the core is much slower allowing blowing agent decomposition, pore nucleation, and growth. Blowing agent particles not only act as gas suppliers but also represent pore nuclei. Thus, microcellular foam cores can be attained by increasing the number of MgH particles. But increasing the number of powder particles by powder milling strongly decreases the flowability and strong particle agglomeration as a result of the increasing cohesive forces leads to inhomogeneous foams. Flowability of the powder can be restored by coating it with SiO-nano-particles resulting in a homogeneous microcellular foam morphology. © 2013 Springer Science+Business Media New York.

A novel process chain for the production of spherical sls polymer powders with good flowability - Schmidt, Jochen; Sachs, Marius; Blümel, Christina; Winzer, Bettina; Toni, Franziska; Wirth, Karl-Ernst; Peukert, Wolfgang (Proceedings of the 7th World Congress on Particle Technology, WCPT 2014, 2015)
Rapid prototyping has been applied so far in the production of special parts at low piece numbers. Currently, rapid prototyping gradually is transferred to additive manufacturing opening new applications. Especially selective laser sintering (SLS) applying polymer powder systems is promising. In the case of SLS basically only polyamide is available as an optimized powder material showing satisfying behavior during processing. Other types of polymer powders produced by cryogenic grinding show poor powder flowability as well as an unfavorable particle habitus resulting in poor device quality. In fact, it is challenging to produce laser sintering powders with small particle size, good flowability and processability. Within this account we present a novel process route for the production of spherical polymer micron-sized particles of good flowability. The feasibility of the process chain is demonstrated for polystyrene (PS) and poly butylene terephthalate (PBT) and the increase of powder flowability after the consecutive process steps has been monitored using a tensile strength tester. The influence of particle habitus and surface functionalization on powder flowability and its properties is discussed. In a first step polymer microparticles are produced by a wet grinding method at reduced temperatures. By this approach the mean particle size and the particle size distribution can be tuned between a few microns and several 10 microns and adapted to specific needs. The dependencies of mean product particle size, particle size distribution and grinding kinetics on stressing conditions, system composition and especially process temperature (increase of the brittleness of the polymer vs. increase of dampening of grinding bead motion with decreasing temperature) will be extensively discussed for the polymers PS, PBT, poly oxo methylene (POM) and Poly ether ether ketone (PEEK). The comminution products obtained typically consist of microparticles of irregular shape and poor powder flowability, i.e. these intermediate products are cohesive and thus will show poor SLS processability. An improvement of flowability of the ground polymer particles is achieved in a second step by changing their shape. The irregular particles are rounded using a heated downer reactor. It will be demonstrated that the 'degree' of rounding can be controlled by changing the temperature profile or the residence time. To further improve the flowability of the cohesive spherical polymer microparticles nanoparticles are adhered to the microparticles' surface in a third step. The improvement of powder flowability after the consecutive process steps is remarkable: rounded and dry-coated PS powders exhibit a strongly reduced tensile strength (by a factor 5) in comparison to the tensile strength of the edged PS comminution product. The improved flowability and packing behavior of the polymer powders open new options in SLS processing including the usage of much smaller polymer bead
Keywords: downer reactor; dry particle coating; polymers; selective laser sintering; wet grinding

A novel process route for the production of spherical LBM polymer powders with small size and good flowability - Schmidt, Jochen; Sachs, Marius; Blümel, Christina; Winzer, Bettina; Toni, Franziska; Wirth, Karl-Ernst; Peukert, Wolfgang (Powder Technology, 2014)
Rapid prototyping has been applied so far in the production of special parts at low piece numbers. Currently, 'rapid prototyping' gradually is transferred to additive manufacturing opening new applications. At present basically only polyamide (PA) is available as an optimized powder material showing satisfying behavior during processing in laser beam melting (LBM). Other types of polymer powders produced by cryogenic grinding show poor powder flowability as well as an unfavorable particle habitus resulting in poor device quality. In fact, it is challenging to produce laser sintering powders with small particle size, good flowability and processability. We present a novel process chain for the production of spherical polymer micron-sized particles of good flowability that can be applied to a large variety of polymers: in a first step polymer particles are produced by a wet grinding method that are rounded in a second step using a heated downer reactor. To increase the flowability of the cohesive spherical polymer particles further nanoparticles are adhered to the particle surface in the third step. We demonstrate an increase of powder flowability by a factor of 5. The influence of particle habitus and nanoparticle functionalization on powder flowability is discussed in detail. © 2014 Elsevier B.V.
Keywords: Downer reactor; Dry particle coating; Flowability; Laser beam melting (LBM); Polymers; Wet grinding

A novel process route for the production of spherical SLS polymer powders - Schmidt, Jochen; Sachs, Marius; Blümel, Christina; Winzer, Bettina; Toni, Franziska; Wirth, Karl-Ernst; Peukert, Wolfgang (Proceedings of PPS-30 : the 30th International Conference of the Polymer Processing Society : conference papers : 6-12 June 2014, Cleveland, Ohio, USA, 2015)
Currently, rapid prototyping gradually is transferred to additive manufacturing opening new applications. Especially selective laser sintering (SLS) is promising. One drawback is the limited choice of polymer materials available as optimized powders. Powders produced by cryogenic grinding show poor powder flowability resulting in poor device quality. Within this account we present a novel proceb route for the production of spherical polymer micron-sized particles of good flowability. The feasibility of the proceb chain is demonstrated for polystyrene e. In a first step polymer microparticles are produced by a wet grinding method. By this approach the mean particle size and the particle size distribution can be tuned between a few microns and several 10 microns. The applicability of this method will be discubed for different polymers and the dependencies of product particle size distribution on strebing conditions and proceb temperature will be outlined. The comminution products consist of microparticles of irregular shape and poor powder flowability. An improvement of flowability of the ground particles is achieved by changing their shape: they are rounded using a heated downer reactor. The influence of temperature profile and residence time on the product properties will be addrebed applying a viscous-flow sintering model. To further improve the flowability of the cohesive spherical polymer particles nanoparticles are adhered onto the microparticles' surface. The improvement of flowability is remarkable: rounded and dry-coated powders exhibit a strongly reduced tensile strength as compared to the comminution product. The improved polymer powders obtained by the proceb route proposed open new pobibilities in SLS procebing including the usage of much smaller polymer bead
Keywords: Downer reactor; Poly butylene terephthalate (PBT); Poly oxo methylene (POM); Polystyrene (PS); Rounding; Selective laser sintering (SLS); Wet grinding; rounding

Attractive particle interaction forces and packing density of fine glass powders - Ribeiro Parteli, Eric Josef; Schmidt, Jochen; Blümel, Christina; Wirth, Karl-Ernst; Peukert, Wolfgang; Pöschel, Thorsten (Scientific Reports, 2014)
We study the packing of fine glass powders of mean particle diameter in the range (4-52)μm both experimentally and by numerical DEM simulations. We obtain quantitative agreement between the experimental and numerical results, if both types of attractive forces of particle interaction, adhesion and non-bonded van der Waals forces are taken into account. Our results suggest that considering only viscoelastic and adhesive forces in DEM simulations may lead to incorrect numerical predictions of the behavior of fine powders. Based on the results from simulations and experiments, we propose a mathematical expression to estimate the packing fraction of fine polydisperse powders as a function of the average particle size.

Dry particle coating for tailor-made product properties: Coating and decoating processes - Blümel, Christina; Wirth, Karl-Ernst (PARTICLE TECHNOLOGY FORUM. 2013. CORE PROGRAMMING AREA AT THE 2013 AICHE ANNUAL MEETING: GLOBAL CHALLENGES FOR ENGINEERING A SUSTAINABLE FUTURE, 2013)

Dry particle coating of polymer particles for tailor-made product properties - Blümel, Christina; Schmidt, Jochen; Dielesen, Andrea; Sachs, Marius; Winzer, Bettina; Peukert, Wolfgang; Wirth, Karl-Ernst (AIP Conference Proceedings 1593, 2014)
Disperse polymer powders with tailor-made particle properties are of increasing interest in industrial applications such as Selective Laser Beam Melting processes (SLM). This study focuses on dry particle coating processes to improve the conductivity of the insulating polymer powder in order to assemble conductive devices. Therefore PP particles were coated with Carbon Black nanoparticles in a dry particle coating process. This process was investigated in dependence of process time and mass fraction of Carbon Black. The conductivity of the functionalized powders was measured by impedance spectroscopy. It was found that there is a dependence of process time, respectively coating ratio and conductivity. The powder shows higher conductivities with increasing number of guest particles per host particle surface area, i.e. there is a correlation between surface functionalization density and conductivity. The assembled composite particles open new possibilities for processing distinct polymers such as PP in SLM process. The fundamentals of the dry particle coating process of PP host particles with Carbon Black guest particles as well as the influence on the electrical conductivity will be discussed.<br
Keywords: agglomeration; dry particle coating; conductivity; percolation; impedance spectroscopy

Increasing flowability and bulk density of PE-HD powders by a dry particle coating process and impact on LBM processes - Blümel, Christina; Sachs, Marius; Laumer, Tobias; Winzer, Bettina; Schmidt, Jochen; Schmidt, Michael; Peukert, Wolfgang; Wirth, Karl-Ernst (Rapid Prototyping Journal, 2015)
Purpose - The purpose of this paper is to demonstrate the processability of cohesive PE-HD particles in laser beam melting processes (LBM) of polymers. Furthermore, we present a characterization method for polymer particles, which can predict the quality of the powder deposition via LBM processes. Design/methodology/approach - This study focuses on the application of dry particle coating processes to increase flowability and bulk density of PE-HD particles. Both has been measured and afterwards validated via powder deposition of PE-HD particles in a LBM machine. Findings - For efficient coating in a dry particle coating process, the PE-HD particles and the attached nanoparticles need to show similar surface chemistry, i.e. both need to behave either hydrophobic or hydrophilic. It is demonstrated that dry particle coating is appropriate to enhance flowability and bulk density of PE-HD particles and hence considerably improves LBM processes and the resulting product quality. Originality/value - At present, in LBM processes mainly polyamide (PA), 12 particles are used, which are so far quite expensive in comparison to, for example, PE-HD particles. This work provides a unique and versatile method for nanoparticulate surface modification which may be applied to a wide variety of materials. After the coating, the particles are applicable for the LBM process. Our results provide a correlation between flowability and bulk density and the resulting product qualit
Keywords: Bulk density; Dry particle coating; Flowability; Hydrophilic; Hydrophobic; Polymers

Numerical study of the packing density of fine powders by means of the Discrete Element Method - Blümel, Christina; Ribeiro Parteli, Eric Josef; Schmidt, Jochen; Wirth, Karl Ernst; Peukert, Wolfgang; Pöschel, Thorsten (85th Annual Meeting of the International Association of Applied Mathematics and Mechanics – GAMM 2014, 2014)
Numerical simulations by means of the Discrete Element Method (DEM) can provide a helpful tool in the investigation of the packing behavior of powders. In this type of numerical simulations, the Newton’s equations of motion for every single particle in the system are solved by taking into account all forces and torques acting on it, both due to external fields and due to interactions with other particles in the system

Rounding of irregular polymer particles in a downer reactor - Sachs, Marius; Schmidt, Jochen; Toni, Franziska; Blümel, Christina; Winzer, Bettina; Peukert, Wolfgang; Wirth, Karl-Ernst (Procedia Engineering 102, 2015)
In the past additive manufacturing processes relying on beam-based methods such as selective laser sintering (SLS) of polymers were almost exclusively applied for the generation of prototypes. In recent years, however, these methods are increasingly applied in the serial production of e.g. special parts to be used in the automotive industry. With this increased relevance in industrial applications, the demands on the powder material increased as well [1]. The so far used polymer materials show weak performance regarding the mechanical stability of processed parts. In consequence, there is a need for fine powders of different polymers showing good powder flowability and high bulk density. Currently, the commercial availability of polymer powders for SLS is very limited and the production processes are still not reliable enough due to poor powder characteristics. Within this contribution a process for the production of spherical polymer micro particles showing good powder flowability is presented [2]. It has been recently shown [3] for different materials that commercially available polymer granules can be ground down to the micron size range by a wet grinding process. Due to the grinding process the produced micron-sized particles are in a chiseled state, which leads to a bad flowability of the powder material. To overcome this problem the single particles are melted in a heated downer reactor and spherical particles are obtained by using the effect of the surface tension [3]. The rounding of ground PS microparticles was performed in a downer reactor with a length of 1,600 mm and a diameter of 25 mm. The reactor temperature was set 100 °C above the melting temperature of the treated material. The laminar flow regime in the downer reactor allows a well-defined residence time of particles and the surrounding gas [4]. The design of the downer reactor allows transferring the polymer particles in the molten state whilst avoiding contact between the single particles and between molten particles and the reactor wall. The mechanism of the rounding process in dependence of particle size, interfacial tension and melt viscosity will be shown within a sintering model [6]. The influence of residence time and overall solids density in the downer reactor on the particle shape and on the flowability of the bulk material is shown. Estimates from the sintering model allow for a reliable reactor design.<br
Keywords: additive manufacturing; particle rounding; downer reactor; polymers